2002
DOI: 10.1016/s0735-1097(02)01967-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered myocardial fatty acid and glucose metabolism in idiopathic dilated cardiomyopathy

Abstract: Patients with IDCM exhibit alterations in myocardial metabolism characterized by decreased fatty acid metabolism and increased myocardial glucose metabolism, a pattern similar to that shown in animal models of HF. Whether alterations in myocardial metabolism constitute an adaptive response or mediate the development of HF remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
284
5
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(321 citation statements)
references
References 32 publications
23
284
5
4
Order By: Relevance
“…Of note, in patients with heart failure, including DCM and ischemic heart disease, FAO is reduced but glucose metabolism is favored, recapitulating the fetal metabolic program. These changes are associated with diminution of Ppargc1a and Esrra expression (31,32). The signals leading to their down-regulation during heart failure are still elusive (33), although MYC has been proposed as a potential upstream repressor of Ppargc1a transcription (34).…”
Section: Dissection Of Moribund Med30mentioning
confidence: 99%
“…Of note, in patients with heart failure, including DCM and ischemic heart disease, FAO is reduced but glucose metabolism is favored, recapitulating the fetal metabolic program. These changes are associated with diminution of Ppargc1a and Esrra expression (31,32). The signals leading to their down-regulation during heart failure are still elusive (33), although MYC has been proposed as a potential upstream repressor of Ppargc1a transcription (34).…”
Section: Dissection Of Moribund Med30mentioning
confidence: 99%
“…According to some studies, PCOS patients have an increased risk for diabetes mellitus [1,2] and often show an adverse cardiovascular risk profile -increased rate of arterial hypertension [3,4], dislipidemia [4][5][6][7] and subclinical inflammation and atherosclerosis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…68,69 METABOLIC IMAGING In patients with a hypertrophic or dilated LV cardiomyopathy, PET imaging has shown that the predominant metabolic substrate of the LV has switched from fatty acids to glucose metabolism, thereby preserving the adenosine triphosphate supply for force generation. [70][71][72] In line with these findings, single-photon emission tomography (SPECT) imaging has demonstrated that, in the hypertrophied RV of patients with PH, myocardial fatty acid uptake was decreased. 73 Although it has been shown that measuring myocardial glucose metabolism using PET with 18 F-2-deoxy-2-fluoro-D-glucose ( 18 FDG) tracers is feasible in patients with PAH, 74 inconsistent results have been reported.…”
Section: Regional Rv Function and Strainmentioning
confidence: 93%